Climate change, population trends and groundwater in Africa - Carter, Richard C.; Parker, Alison (Intl Assn of Hydrological Sciences Press, 2009)
Global climate change is affecting Africa, as it is every other continent and region of the world. The absolute poverty of a large proportion of the continent's people renders them highly vulnerable to changes in climate. Mitigation of climate change is a global imperative. However, numerous other changes continue apace, notably population growth, natural resource degradation, and rural-urban migration. Probably 50% or more of the continent's population rely on groundwater. This paper explores the relative impacts of changes in climate, demography and land use/cover on groundwater resources and demands. It concludes that the climate change impacts are likely to be significant, though uncertain in direction and magnitude, while the direct and indirect impacts of demographic change on both water resources and water demand are not only known with far greater certainty, but are also likely to be much larger. The combined effects of urban population growth, rising food demands and energy costs, and consequent demand for fresh water represent real cause for alarm, and these dwarf the likely impacts of climate change on groundwater resources, at least over the first half of the 21st century.